A framework to model and analyze the performability of mobile software systems. - Bracchi, Paola (Software engineering notes.)
The early validation of non-functional requirements of software systems is becoming a very stringent concern, especially in two domains: heterogeneous computing environments and interactive systems. In the former case the issue arises from the need of effectively exploiting the resources and capabilities that those environments may provide. In the latter case non-functional attributes (such as performance, reliability and availability) are peculiar for guaranteeing high levels of quality of services to users. Mobile software systems (e.g. web connected mobile phones) embrace both domains and therefore claim for accurate nonfunctional validation since the early phases of the software development process.This paper focuses on model based analysis of the performability of mobile software systems. We introduce a general framework that encompasses performance, dependability and mobility of software systems and that supports the specification and estimate of performability measures. The framework is based on the Stochastic Activity Networks notation. We also show the viability of our approach at work on a simple network management scenario.